Kajian Pemenuhan Kebutuhan Nutrien dan Energi pada Kuda Bunting dan Laktasi di Peternakan Kuda di Bogor: Study of Nutrient Requirement and Feeding of Pregnant and Lactating Mares in Several Stable in Bogor - Alma Agnia; Dewi Apri Astuti; Yuli Retnani (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
This study aimed to determine the nutrient and energy requirement in pregnant and lactating mares. This study used an observation methodology and it was conducted on eight stables with 11 pregnant mares and 16 lactating mares. Observed variables included mare profile (estimated body weight, horse type, physiological condition (pregnancy or lactation), feeding (type of feed, amount of feed, nutrient content, total feed consumption) then compared with nutrient requirement based on NRC (2007). Data on feed consumption were collected based on different physiological conditions (pregnancy and lactation) and body weight. Given feed was analysed by proximate analysis. The results of this study showed that the nutrient consumption of pregnant and lactating mares on one stable did not meet the overall requirement, three stables had not met the energy requirement and two stables had higher ratio of Ca:P to P. Key words: lactating mare, mare, mare feed, nutrient, pregnant mare